Catalytic conversion of corncob and corncob pretreatment hydrolysate to furfural in a biphasic system with addition of sodium chloride. (February 2017) - Qing, Qing; Guo, Qi; Zhou, Linlin; Wan, Yilun; Xu, Youqing; Ji, Huilong; Gao, Xiaohang; Zhang, Yue
Highlights: An efficient biphasic catalytic system was developed for furfural production. A highest furfural yield of 81.7% was achieved under optimized conditions. 66.1% furfural and 15.9% HMF yields were obtained from raw corncob in this catalytic system. The SO4 2− /SnO2 − MMT catalyst displayed good recyclability and stability in this system. Abstract: Catalytic conversion of corncob pretreatment hydrolysate and raw corncob into furfural in a modified biphasic system by SO4 2− /SnO2 − MMT solid catalyst has been developed. The influence of the organic solvent type, organic to water phase ratio, sodium chloride concentration, reaction temperature and time on the furfural production were comparatively evaluated. The results showed that furfural yields of 81.7% and 66.1% were achieved at 190 °C for 15 mins and 190 °C for 20 mins, respectively, for corncob pretreatment hydrolysate and raw corncob by this solid catalyst. The solid catalyst used in this study exhibited good stability and high efficiency applied in the modified biphasic system in addition to excellent recyclability. The proposed catalytic system displayed high performance for catalytic conversion of lignocellulosic biomass into important platform chemicals and has great potential in industrial application.